The beneficial effects of the composite probiotics from camel milk on glucose and lipid metabolism, liver and renal function and gut microbiota in db/db mice - Tabusi Manaer; Lan Yu; Xin-Hua Nabi; Dinareer Dilidaxi; Lu Liu; Jialehasibieke Sailike (BMC, 2021)
Abstract Background Probiotics may have beneficial effects on patients with type 2 diabetes mellitus (T2DM). We separated 4 lactobacillus and 1 saccharomycetes from traditional fermented cheese whey (TFCW) and prepared composite probiotics from camel milk (CPCM) and investigated their effects on glucose and lipid metabolism, liver and renal function and gut microbiota in db/db mice. Methods CPCM was prepared in the laboratory and 40 db/db mice were randomly divided into 4 groups as metformin, low-dose and high-dose group and model group, and treated for 6 weeks. In addition, 10 C57BL/Ks mice as normal control group were used for comparison. Fasting blood glucose (FBG), body weight (BW), oral glucose tolerance test (OGTT), glycated hemoglobin (HbAlc), C-peptide (CP), triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), 24 h urinary microalbumin (24 h malb), urine ketone, urine sugar, pancreas and liver tissue and intestinal flora were tested. Results Compared to diabetic group, high dose CPCM significantly decreased FBG, OGTT, HbAlc and IRI, plasma TC, TG, LDL-C, 24 h malb, urine ketone and urine sugar, increased CP, HDL-C levels, improved the liver and kidney function, protected the function of islets, also increased intestinal tract lactic acid bacteria and Bifidobacterium, decreased Escherichia in db/db mice. Conclusion CPCM decreased FBG, OGTT and HbAlc, increased CP, modulated lipid metabolism and improved liver and kidney protected injury in db/db mice, which may be related to various probiotics acting through protecting the function of islets and regulating intestinal flora disturbance.